Handbook of psychotherapy integration - Norcross, John C., 1957-; Goldfried, Marvin R. (Oxford series in clinical psychology., 2005)
Seasoned psychotherapists realize that no single theory or unitary treatment can ever suffice for all patients, disorders, and situations. This volume provides a comprehensive description and illustration of psychotherapy integration by leading proponents.